Experiments on substrate choice and feeding efficiency of downy Tufted ducklings Aythya fuligula - Giles, N (Wildfowl, 1989)
Two series of trials were carried out on broods of laboratory-reared downy Tufted ducklings. In the first trial the birds fed on snails and bivalves significantly more often over open gravel substrates than amongst lily or hornwort beds. Mean dive durations gradually increased from c.2 to c.5 seconds with age. In the second series of trials a brood of ducklings located and exploited a small food patch in an otherwise featureless tank. The brood learnt rapidly to concentrate dives over the food patch and achieved a feeding success rate of one chironomid larva per dive at a prey density of 2000/m. When the food density was doubled, the feeding success rate (chironomid larvae eaten per dive) also doubled whilst the dive duration (c.2 seconds) and the proportion of dives directed at the food patch (c.25%) remained constant. The value to diving ducklings of increased food availability within the brood-rearing habitat is discussed.